2023
DOI: 10.1101/2023.10.11.561954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Keratin 17- and PKCα-dependent transient amplification of neutrophil influx after repeated stress to the skin

Yang Xu,
Erez Cohen,
Craig N. Johnson
et al.

Abstract: Neutrophils contribute to the pathogenesis of chronic inflammatory skin diseases. Little is known about the source and identity of the signals mediating their recruitment in inflamed skin. We used the phorbol ester TPA and UVB, alone or in combination, to induce sterile inflammation in mouse skin and assess whether keratinocyte-derived signals impact neutrophil recruitment. A single TPA treatment results in a neutrophil influx in the dermis that peaks at 12h and resolves within 24h. A second TPA treatment or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…We found that neutrophil infiltration peaks at 12 h and returns to basal levels by 48 h ( Fig. 6e-g ) - kinetics that align with previous studies 6769 . The absence of Ly6G staining on the ventral (untreated) side of the ear indicates that neutrophil infiltration occurs in the tissue proximal to the TPA-treated area.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We found that neutrophil infiltration peaks at 12 h and returns to basal levels by 48 h ( Fig. 6e-g ) - kinetics that align with previous studies 6769 . The absence of Ly6G staining on the ventral (untreated) side of the ear indicates that neutrophil infiltration occurs in the tissue proximal to the TPA-treated area.…”
Section: Resultssupporting
confidence: 91%
“…To assess the effect of secreted DNA on the kinetics of neutrophil infiltration in vivo , we took advantage of a well-established model of acute skin inflammation in mice, induced by topical application of a phorbol ester, tetradecanoylphorbol-13-acetate (TPA) 66,67 . The primary targets of topically applied TPA are the suprabasal differentiating keratinocytes of the epidermis 67 . DNase I or PBS control, was injected in the tail vein one hour prior to topical TPA treatment on the dorsal ear skin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation